Negative Health Effects of Excessive Alcohol Consumption: A Systematic Review - Rubiah, Ajan; Vivien, Yew Wong Chin; Abd Hair, Awang (Malaysian Journal of Social Sciences and Humanities, 2021)
Drinking alcohol is one of the risk that faces the society, and the public health authorizes as well as the economics of countries. Several studies were conducted to understand the status of alcohol consumption. However, few studies reviewed the literature to identify the status quo of alcohol. This study aims to review the literature related to alcohol consumption. Keywords that are related to the topic were used to search for articles in reliable databases. The articles were filtered based on time, scope, language, and index. A timeframe of four years was used to have an update view of the consumption of alcohol. Only English articles related to alcohol consumption were used. The results of this systematic literature review indicate that most of the previous studies are quantitative. In addition, the result also showed that there is limited studies in developing countries. Social, economic and family related issues are consequence of excessive consumption of alcohol. There is a need for more studies in non-western context to understand the status and possible remedy for alcohol consumption.